Strategi Badan Pegusahaan Batam Dalam Pengelolaan Impor Barang Dikawasan Free Trade Zone (FTZ) - Sehan Amanda; Khairi Rahmi; Ardi Putra (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2025)
The management of imported goods in the Batam Free Trade Zone and Free Port (KPBPB Batam) plays a strategic role in sustaining industrial activities; however, its implementation continues to face recurring administrative and coordination constraints despite an established regulatory framework, prompting this study to analyze policy implementation, identify operational barriers, and examine BP Batam’s strategies using the Van Meter and Van Horn policy implementation theory focusing on inter-organizational communication, resources, and implementing agency characteristics through a qualitative descriptive approach based on regulatory documents, policy records, and business complaint data from the BP Batam B-Care system, with findings indicating that import management has generally complied with regulations and is supported by the I-BOSS system, yet persistent challenges remain due to administrative complexity, technical system issues, limited understanding among business actors, and insufficiently integrated inter-agency coordination, highlighting an implementation gap at the operational level.